PENYULUH BAHASA BALI SEBAGAI PENYELEMAT BAHASA BALI YANG “MENARI” DI ATAS “LUBANG KUBUR” - Made Swartama Putra (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2020)
Language is a means of communication which is able to use communicate with other people around us. By language, human is able to express something which appear in their heart and thought. Language is a sound symbol system that is used by a society to cooperate, interact, self identification and express the content of thought.Many problems can be found in the society about balinese language. Starting from writing of balinese script till the writing of word or sentence of balinese language. For example, many names of public places which are writen by balinese language are still incorrect. As well in writing of word and sentence by using balinese language in communicatingor chating, for example the word “sing”, “dija”, “apa”, many balinese people make a mistake in writing those words in chatting by writing “seng”, “dije”, “ape”As a speaker of balinese language, balinese people cannot ignore these problems wich occured in the society related to balinese language. These problems must become our attention because if we ignore them, it will become a time bomb which harm the happiness of balinese language.The extension agent is expected to become a savior of balinese language. Continuity and be able to solve the problem that occured in the society especially related to balinese language. The cooperation is required between the extension agent, speaker dan also the tacher to save balinese language. Keyword :Language, Bali, Balinese Language, extension agent, problem, speaker, balinese society, society, community